Innovations in designing microwave electro-technological units with hybrid chambers - TUHVATULLIN, Midhat; ARKHANGELSKY, Yuri; AIPOV, Rustam; KHASANOV, Eduard (Spanish Journal of Agricultural Research, 2023)
Aim of study: Microwave (MW) electro-technological units based on electromagnetic radiation of ultrahigh-frequency can involve thermal MW modification of dielectrics and non-thermal MW modification of polymers. Area of study: Russian Federation.Material and methods: The paper considers a method for making a unit with a hybrid chamber, where thermal and non-thermal MW modifications were carried out simultaneously, and the remaining energy after non-thermal MW modification of polymers was used for heating the dielectric. Main results: A microwave electro-technological unit with a hybrid chamber replaced two separate devices that implemented these MW modifications. It was cheaper and required one MW generator. The unit took up less space than two separate apparatuses, and upgraded the existing microwave dryer to perform thermal MW modification of a lumber pile and non-thermal MW modification of polymer materials. The existing microwave dryer was redeveloped by solving the boundary value problem in electrodynamics and heat and mass transfer. Research highlights: The research presents a microwave electro-technological unit with a hybrid chamber, combining thermal and non-thermal MW modifications of dielectric and polymer materials. As a result of upgrading the existing microwave dryer, it was possible to carry out both thermal and non-thermal MW modifications, namely, microwave drying of timber and microwave drying of up to seven different polymer objects.